Peanut research and poverty reduction: Impacts of variety improvement to control peanut viruses in Uganda - Moyo, Sibusiso; Norton, George W.; Alwang, Jeffrey; Rhinehart, Ingrid; Deom, C. Michael (Wiley, 2007)
A procedure is developed and applied for predicting ex ante impacts of agricultural research on aggregate poverty, using as an example the poverty‐reducing impact of peanut research in Uganda. Market‐level information on economic surplus changes is combined with a procedure for allocating income changes to individual households. Characteristics of farmers that affect their likelihood of technology adoption are used to create a technology adoption profile. Associated changes in poverty resulting from adoption are computed using poverty indices. Predicted income changes at the household level are aggregated to the market level and reconciled with calculations of economic surplus changes.